Endocytosis of Mycobacterium tuberculosis Heat Shock Protein 60 Is Required to Induce Interleukin-10 Production in Macrophages - Parveen, Nazia (American Society for Biochemistry and Molecular Biology, 2013)
Understanding the signaling pathways involved in the regulation of anti-inflammatory and pro-inflammatory responses in tuberculosis is extremely important in tailoring a macrophage innate response to promote anti-tuberculosis immunity in the host. Although the role of toll-like receptors (TLRs) in the regulation of anti-inflammatory and pro-inflammatory responses is known, the detailed molecular mechanisms by which the Mycobacterium tuberculosis bacteria modulate these innate responses are not clearly understood. In this study, we demonstrate that M. tuberculosis heat shock protein 60 (Mtbhsp60, Cpn60.1, and Rv3417c) interacts with both TLR2 and TLR4 receptors, but its interaction with TLR2 leads to clathrin-dependent endocytosis resulting in an increased production of interleukin (IL)-10 and activated p38 MAPK. Blockage of TLR2-mediated endocytosis inhibited IL-10 production but induced production of tumor necrosis factor (TNF)-α and activated ERK1/2. In contrast, upon interaction with TLR4, Mtbhsp60 remained predominantly localized on the cell surface due to poorer endocytosis of the protein that led to decreased IL-10 production and p38 MAPK activation. The Escherichia coli homologue of hsp60 was found to be retained mainly on the macrophage surface upon interaction with either TLR2 or TLR4 that triggered predominantly a pro-inflammatory-type immune response. Our data suggest that cellular localization of Mtbhsp60 upon interaction with TLRs dictates the type of polarization in the innate immune responses in macrophages. This information is likely to help us in tailoring the host protective immune responses against M. tuberculosis.